Analisis Keuntungan Pemasaran Bunga Potong Krisan di Surabaya - Adellya Putri Sugiharto; Koesriwulandari Koesriwulandari; Markus Patiung (Study Program of Agribusiness, Faculty of Agriculture, University of Wijaya Kusuma Surabay, 2022)
The purpose of this study is: to analyze marketing costs, analyze profits in marketing and analyze the factors that influence the marketing advantages of cut chrysanthemum flowers in the Kayoon flower market Surabaya. The research method used is simple random sampling. The respondents in this study were 30 merchants retailers of chrysanthemum cut flowers. The data analysis method uses multiple linear regression analysis. Based on the results of multiple linear regression, the profit mode of marketing chrysanthemum cut flowers in the Kayoon Surabaya flower market is as follows: Y = 3991783,723 – 26,846X1 – 6,587X2 + 0.292X3 + 23,633X4 + e. F-statistical value with a magnitude of 2,941 or above the significance level of 0.05 (α = 5%). It was concluded that all marketing activities carried out simultaneously including stand rental financing, transportation financing, levy financing, labor financing have a significant influence with the profits obtained from efforts to market discounts from chrysanthemum flowers at the Kayoon Surabaya flower market. Partially, marketing activities that have a significant influence on the profits obtained from marketing efforts are stand rental financing and transportation financing and labor financing.Keywords: Chrysanthemum Cut Flowers, Marketing Advantage, Multiple Linear Regression